2018
DOI: 10.1136/jnnp-2017-317793
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain and tau concentrations are markedly increased in the serum of patients with sporadic Creutzfeldt-Jakob disease, and tau correlates with rate of disease progression

Abstract: ObjectivesA blood-based biomarker of neuronal damage in sporadic Creutzfeldt-Jakob disease (sCJD) will be extremely valuable for both clinical practice and research aiming to develop effective therapies.MethodsWe used an ultrasensitive immunoassay to measure two candidate biomarkers, tau and neurofilament light (NfL), in serum from patients with sCJD and healthy controls. We tested longitudinal sample sets from six patients to investigate changes over time, and examined correlations with rate of disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 40 publications
7
70
3
2
Order By: Relevance
“…The elevated levels of t‐PrP already present at the initial stages of the disease support its potential role as an early clinical diagnostic biomarker. Regarding clinical phenotype, although total‐tau and NFL correlate with disease progression rate in CJD and AD, respectively , we did not observe an association between t‐PrP and disease duration, which does not support the utility of plasma t‐PrP as marker for prognosis or disease monitoring.…”
Section: Discussionmentioning
confidence: 75%
“…The elevated levels of t‐PrP already present at the initial stages of the disease support its potential role as an early clinical diagnostic biomarker. Regarding clinical phenotype, although total‐tau and NFL correlate with disease progression rate in CJD and AD, respectively , we did not observe an association between t‐PrP and disease duration, which does not support the utility of plasma t‐PrP as marker for prognosis or disease monitoring.…”
Section: Discussionmentioning
confidence: 75%
“…Our results are consistent with past studies showing that serum levels of NF-L are higher in people with diverse neurological and neurodegenerative conditions. Researchers have reported that serum levels of NF-L are higher in people with multiple sclerosis (Kuhle et al, 2016;Disanto et al, 2017;Kuhle et al, 2017;Novakova et al, 2017), acute ischemic stroke (De Marchis et al, 2018), active cerebral small vessel disease (Gattringer et al, 2017), familial Alzheimer's disease (Mattsson et al, 2017;Weston et al, 2017), Huntington's disease (Byrne et al, 2017), frontotemporal dementia (Rohrer et al, 2016), Creutzfeldt-Jakob disease (Thompson et al, 2018), Parkinsonian disorders (Hansson et al, 2017), other degenerative ataxias such as multiple system atrophy (Wilke et al, 2018) and amyotrophic lateral sclerosis (Feneberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because older adults are more likely to have neurological conditions prior to brain injury, NF-L might be elevated differentially in older adults, compared to middle-aged or younger adults, following mild traumatic brain injury (MTBI). A number of studies indicate that serum NF-L levels are higher in people with diverse neurological and neurodegenerative diseases (Kuhle et al, 2016;Rohrer et al, 2016;Byrne et al, 2017;Disanto et al, 2017;Gattringer et al, 2017;Hansson et al, 2017;Kuhle et al, 2017;Mattsson et al, 2017;Novakova et al, 2017;Weston et al, 2017;De Marchis et al, 2018;Feneberg et al, 2018;Thompson et al, 2018;Wilke et al, 2018). Therefore, as a potential diagnostic or prognostic biomarker for neurotrauma, it is important to determine whether there is an association between age and NF-L levels in individuals who sustain MTBIs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in prion disease it is important to understand at what disease stage treatment can be effective. Clinically, most prion disease patients die within half a year of first symptoms 36 , and this rapid decline is mirrored by high levels of biofluid neuronal injury and prion seeding biomarkers in the symptomatic phase of disease [37][38][39][40][41][42] . Meanwhile, individuals at risk for genetic prion disease, caused by protein-altering variants in the prion protein gene (PRNP), can be identified through predictive genetic testing when disease onset is on expectation years or decades away 43 , ahead of molecular markers of pathology 44 .…”
Section: Introductionmentioning
confidence: 99%